The Development of Teaching Materials Based on Slip Out on Plants in Class IV SDN Balun I Turi Lamongan - Diana Kusuma Kartika; M. Subandowo; Hari Karyono (Institute of Computer Science (IOCS), 2022)
This study aims to provide teaching materials for fourth grade elementary school students with material on knowing the parts of plants. This teaching material is designed attractively by paying attention to color and writing so that it aims to create a pleasant atmosphere. This study uses the ASSURE model which has 6 stages, namely: (1) Analyze Learner, (2) State Objectives, (3) Select methods, media and materials, (4) Utilize media and materials, (5) Require Learner's participation, (6 ) evaluate and review. This development research uses material expert validation, media expert validation and design expert validation. This research is also supported by the validation of classroom teachers. The subjects of this study were students in the fourth grade of elementary school. Based on the results of the study, it can be concluded: that the product development in the form of elementary science teaching materials with material on knowing the parts of plants based on Slip Out is suitable for use in elementary schools in grade IV.